Extreme root resorption in orthodontic practice: teeth do not have to be replaced with implants - Alberto Consolaro (Dental Press Editora, 2019)
ABSTRACT The replacement of natural teeth that have extreme external apical root resorption, induced by orthodontic treatment, with osseointegrated implants is not justifiable biologically or clinically. These teeth should be preserved and keep their normal functions, as there is no greater mobility, pain or color change. They may undergo usual procedures, such as bleaching, restorations with veneers and other esthetic procedures that may be necessary along life. The pulp of these teeth is normal. If mobility of a tooth with extreme resorption is identified, the cause of mobility should be investigated, as it is not associated with resorption, not even at advanced stages. Tooth mobility may be associated with recent removal of orthodontic appliance, occlusal trauma, chronic inflammatory periodontal disease, or even severe cervical bone loss. In such cases, the cause of mobility should be eliminated and possible sequelae should be corrected, because these, and not root resorption, may actually require retention.